2023
DOI: 10.1161/circimaging.122.014454
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cardiac Magnetic Resonance Imaging in Patients With a Working Diagnosis of MINOCA—An Outcome Study With up to 10 Years of Follow-Up

Abstract: BACKGROUND: Patients with a working diagnosis of myocardial infarction with unobstructed coronary arteries (MINOCA) represent a heterogeneous cohort. The prognosis could vary substantially depending on the underlying cause. Although cardiac magnetic resonance (CMR) is considered a key diagnostic tool in these patients, there are limited data linking the CMR diagnosis with the outcome. METHODS: This study is a prospective outcomes registry of consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Of note, no research has demonstrated that a CMR diagnosis of myocarditis carries a worse prognosis compared to a normal CMR examination in patients with a working diagnosis of MINOCA. Similarly, previous studies have not demonstrated that the diagnosis of AMI is a predictor of mortality in multivariate analysis after accounting for conventional clinical indices (e.g., age, coronary artery disease [CAD] risk factors, troponin levels), despite the fact that patients with MINOCA with a CMR diagnosis of AMI appear to have moderately higher mortality than those with a normal CMR [8,39,40]. The underlying reason for MINOCA could have a significant impact on the prognosis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of note, no research has demonstrated that a CMR diagnosis of myocarditis carries a worse prognosis compared to a normal CMR examination in patients with a working diagnosis of MINOCA. Similarly, previous studies have not demonstrated that the diagnosis of AMI is a predictor of mortality in multivariate analysis after accounting for conventional clinical indices (e.g., age, coronary artery disease [CAD] risk factors, troponin levels), despite the fact that patients with MINOCA with a CMR diagnosis of AMI appear to have moderately higher mortality than those with a normal CMR [8,39,40]. The underlying reason for MINOCA could have a significant impact on the prognosis.…”
Section: Discussionmentioning
confidence: 96%
“…This underscores the significance of CMR for diagnostic and prognostic reasons]. In addition, CMR diagnoses of acute myocardial infarction, myocarditis, and nonischemic cardiomyopathy are independent predictors of poor outcomes [8].…”
Section: Introductionmentioning
confidence: 88%
“…In this issue of Circulation: Cardiovascular Imaging, Konst et al 11 investigate LGE in the setting of myocardial infarction and unobstructed coronary arteries (MINOCA). MINOCA is not rare and occurs in ≈5% of patients with acute myocardial infarction.…”
Section: See Article By Konst Et Almentioning
confidence: 99%